Ten Tips for Performing Your First Peer Review: The Next Step for the Aspiring Academic Plastic Surgeon - Frendø, Martin; Frithioff, Andreas; Andersen, Steven Arild Wuyts (Archives of Plastic Surgery, 2022)
Performing the first peer review of a plastic surgical research article can be an overwhelming task. However, it is an essential scholarly skill and peer review is used in a multitude of settings: evaluation of journal articles, conference abstracts, and research proposals. Furthermore, peer reviewing provides more than just the opportunity to read and help improve other's work: peer reviewing can improve your own scientific writing. A structured approach is possible and recommended.In these ten tips, we provide guidance on how to successfully conduct the first peer reviews. The ten tips on peer reviewing concern: 1) Appropriateness: are you qualified and prepared to perform the peer review? 2) Familiarization with the journal and its reviewing guidelines; 3) Gathering first impressions of the paper followed by specific tips for reviewing; 4) the abstract and introduction; 5) Materials, methods, and results (including statistical considerations); and 6) discussion, conclusion, and references. Tip 7 concerns writing and structuring the review; Tips 7 and 8 describe how to provide constructive criticism and understanding the limits of your expertise. Finally, Tip 10 details why—and how—you become a peer reviewer. Peer review can be done by any plastic surgeon, not just those interested in an academic career. These ten tips provide useful insights for both the aspiring and the experienced peer reviewer. In conclusion, a systematic approach to peer reviewing is possible and recommended, and can help you getting started to provide quality peer reviews that contribute to moving the field of plastic surgery forward.
Keywords: peer review; continuing medical education; plastic surgery